What do software team managers want from a skills identification? - Flauzino, Matheus A.; Souza, Mauricio R. D. A.; Durelli, Vinicius H. S.; Durelli, Rafael S. (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM); 2021: Anais do IX Workshop de Visualização, Evolução e Manutenção de Software, 2021)
Searching for developers with the necessary skills to work effectively on a project is not an easy task for companies. For software team managers, it is important to know their team's experience and what technologies they are using in order to be able to allocate resources optimally. Therefore, in this paper, we decided to study the needs of the managers of a software development company in order to identify their team's skills. We carried out a focus group. We have interviewed 11 managers from a development company (with approximately 75 developers). As result we have mapped 5 issues, 4 possible applications and another 7 needs to create a new methodology for identifying skills. Finally, we conclude that managers are interested in a methodology to identify skills in business flow.